2021
DOI: 10.1515/revneuro-2021-0070
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres: the role of shortening and senescence in major depressive disorder and its therapeutic implications

Abstract: Major depressive disorder (MDD) is one of the most prevalent and debilitating psychiatric disorders, with a large number of patients not showing an effective therapeutic response to available treatments. Several biopsychosocial factors, such as stress in childhood and throughout life, and factors related to biological aging, may increase the susceptibility to MDD development. Included in critical biological processes related to aging and underlying biological mechanisms associated with MDD is the shortening of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 242 publications
0
6
0
Order By: Relevance
“…In a study of 238 participants, aged between 55 and 88 years, they observed a consistent association between short sleep duration, higher latency, and a faster telomere-shortening rate. Regarding the possible biochemical mechanisms that link sleep quality and telomeres, they propose inflammation, oxidative stress, cortisol secretion, and/or increased sympathetic activity [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 238 participants, aged between 55 and 88 years, they observed a consistent association between short sleep duration, higher latency, and a faster telomere-shortening rate. Regarding the possible biochemical mechanisms that link sleep quality and telomeres, they propose inflammation, oxidative stress, cortisol secretion, and/or increased sympathetic activity [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…For metabolic diseases, the possibility of inflammatory deregulation is raised [ 128 ]. The role of telomeres in relation to the HPA axis [ 152 , 153 ] or inflammation [ 125 ] has also been studied. In the present work, the role of telomere length along with BDNF, as an intermediary between loneliness and depression, and its relationship with a worse state of health are discussed.…”
Section: Discussionmentioning
confidence: 99%
“…In a review on the relationship between telomeres and depression, telomeres were noted to shorten with age and changes in telomerase activity were noted in peripheral blood cells and brain tissues in those with major depressive disorder [25]. Other relevant biological mechanisms were noted in this review including HPA axis activity leading to oxidative stress, inflammation, genetic and epigenetic changes.…”
Section: Neurological Involvementmentioning
confidence: 77%
“…Moreover, imbalance between neuroprotective (e.g., brain-derived neurotrophic factor [BDNF], progranulin, cystatin C) and neuroprogressive (e.g., nuclear factor kappa-light-chain-enhancer of activated B cells [NF-κB] and nitric oxide [NO]) factors in favor of the latter bring negative effects [3,4]. Another known cause of depression is telomerase shortening and inflammation, which increases oxidative damage at both the central (brain) and systemic (blood) level [5,6]. Polymorphisms of various genes, including those encoding enzymes of the tryptophan catabolite (TRYCAT) pathway, are also related to overproduction of reactive oxygen species (ROS) [6].…”
Section: Introductionmentioning
confidence: 99%